Analisis Muatan Konten IPAS Terkait Berbagai Jenis Pekerjaan dan Kegiatan Ekonomi pada Buku IPAS Kelas 4 Sekolah Dasar Berbasis HOTS - Wahyuni, Dianisa; Kholillah, Mustika Khoirunnisa; Rustini, Tin (Indonesian Journal Publisher, 2024)
This research aims to determine the social studies content related to various types of work and economic activities in the HOTS-based 4th grade elementary school science books. This research uses a qualitative descriptive research method. This research will only focus on analyzing the social science content content in the Merdeka Curriculum science and science book. The science and science books are analyzed as to which social science content is related to types of work and economic activities. The collected data is then grouped and described in detail regarding the types of work and HOTS-based economic activities.